2019
DOI: 10.15171/mejdd.2019.152
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results of Endoscopic Balloon Dilatation for Gastric Outlet Obstruction Caused by Peptic Ulcer Disease

Abstract: BACKGROUND Gastric outlet obstructions (GOO) is a disabling complication of peptic ulcer disease (PUD). The introduction of endoscopic through the scope balloon dilatation (EBD) has eased the management but there are few reports on the long term results of this modality of treatment on patients’ symptoms. METHODS Over a period of 4 years from January 2012 to December 2015 in two major referral hospitals affiliated to Shiraz university, medical endoscopy reports were reviewed retrospectively to identify those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…2,4,6,10 Regarding endoscopic dilation, surgery is indicated if the pylorus is obstructed and cannot be safely dilated, or if the obstruction persists or recurs despite endoscopic dilations to achieve a diameter of 15 mm, symptoms usually improve considerably with successful dilation of 12 to 15 mm. 3 In the case presenting with the recurrence of AHPS and the impossibility of dilating it Some authors prefer partial gastrectomy with Billroth I reconstruction because carcinoma can be a complication of long-standing pyloric hypertrophy. 5,6 Approximately 25 percent of gastric cancer patients have a history of gastric ulcer related to Helicobacter pylori infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,6,10 Regarding endoscopic dilation, surgery is indicated if the pylorus is obstructed and cannot be safely dilated, or if the obstruction persists or recurs despite endoscopic dilations to achieve a diameter of 15 mm, symptoms usually improve considerably with successful dilation of 12 to 15 mm. 3 In the case presenting with the recurrence of AHPS and the impossibility of dilating it Some authors prefer partial gastrectomy with Billroth I reconstruction because carcinoma can be a complication of long-standing pyloric hypertrophy. 5,6 Approximately 25 percent of gastric cancer patients have a history of gastric ulcer related to Helicobacter pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…2 Chronic peptic ulcer resulting in gastric outlet obstruction is the least common complication, occurring in approximately 2 percent of cases. 3 Patients with secondary AHPS often do not present any symptoms. 4 Diagnosing hypertrophic stenosis in adults remains a challenge; differentiation between primary and secondary pyloric stenosis is made by histopathological report.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors reported that the introduction of endoscopic balloon dilation has simplified the treatment of benign gastric outlet obstruction due to peptic ulcer disease and is associated with favourable long-term outcome. Moreover, it is now considered to be the first-line treatment [ 3 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relapses are less common after successful eradication of H. pylori (26) . Clinical improvement after endoscopic balloon dilation is estimated at about 70% (27) . In the absence of H. pylori infection, the rate of endoscopic failures is higher.…”
Section: Peptic Ulcer Disease Of the Stomach And Duodenummentioning
confidence: 99%